2020
DOI: 10.1182/bloodadvances.2020001584
|View full text |Cite
|
Sign up to set email alerts
|

PI3Kδ inhibition reshapes follicular lymphoma–immune microenvironment cross talk and unleashes the activity of venetoclax

Abstract: Despite idelalisib approval in relapsed follicular lymphoma (FL), a complete characterization of the immunomodulatory consequences of phosphatidylinositol 3-kinase δ (PI3Kδ) inhibition, biomarkers of response, and potential combinatorial therapies in FL remain to be established. Using ex vivo cocultures of FL patient biopsies and follicular dendritic cells (FDCs) to mimic the germinal center (n = 42), we uncovered that PI3Kδ inhibition interferes with FDC-induced genes related to angiogenesis, extracellular ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 56 publications
2
30
0
Order By: Relevance
“…FL-FDC cross-talk induces a pro-angiogenic expression pattern in FL cells, including secretion of VEGF-A and VEGF-C ( 255 ). This cross-talk is crucially dependent on the phosphoinositide-3-kinase δ (PI3Kδ), providing therapeutic intervention options with PI3K specific inhibitors like idelalisib, which is approved for the treatment of FL, CLL, and SLL ( 256 ). The second branch of the supportive infrastructure in follicles are the CD4 + CXCR5 + PD1 + T follicular helper (Tfh) cells, which provide vital survival signals for FL cells by secreting IL2, IL4, IFNγ, and by CD40L presentation ( 9 , 257 ).…”
Section: B Cell Lymphoma-induced Vascular Changes Are Dependent On Thmentioning
confidence: 99%
“…FL-FDC cross-talk induces a pro-angiogenic expression pattern in FL cells, including secretion of VEGF-A and VEGF-C ( 255 ). This cross-talk is crucially dependent on the phosphoinositide-3-kinase δ (PI3Kδ), providing therapeutic intervention options with PI3K specific inhibitors like idelalisib, which is approved for the treatment of FL, CLL, and SLL ( 256 ). The second branch of the supportive infrastructure in follicles are the CD4 + CXCR5 + PD1 + T follicular helper (Tfh) cells, which provide vital survival signals for FL cells by secreting IL2, IL4, IFNγ, and by CD40L presentation ( 9 , 257 ).…”
Section: B Cell Lymphoma-induced Vascular Changes Are Dependent On Thmentioning
confidence: 99%
“…We have established primary FL-FDC co-cultures using FL samples mostly from LN biopsies (composed mainly by tumor B cells and several T subpopulations including TFH, regulatory, and cytotoxic T cells) and supportive FDC (HK cell line) generated from tonsils of normal donors previously used to mimic de GC [22] and promote B-cell survival [23]. Using this primary co-culture model, we previously reported that FL-FDC crosstalk shapes key lymphoma features including adhesion, dissemination, angiogenesis, and ECM remodeling, among others [21,39].…”
Section: Discussionmentioning
confidence: 99%
“…The net balance of these effects might result in inefficient crosstalk between FL cells and the supportive T FH cells. Moreover, the chemokine CCL22, fundamental in the FL milieu, decreases after idelalisib treatment, and this phenomenon impacts on the composition of FL microenvironment by a decrease in the recruitment of T REG and T FH , but not T FR into FL-FDC niche, which may allow the host to mount superior immune responses against the tumor [ 60 ].…”
Section: T Cells: Fundamental Actors In Fl Pathogenesis Modulated mentioning
confidence: 99%